Efficacy of a papain-based gel from indigenous papaya (Carica papaya L., var. Solo) for chemomechanical caries removal - Echegoyen, Trisha Eiko M.; Lozano, Florentino Kurt, III P.; Nano, Jocelyn A.; Alfaro, Arlene Cecilia A. (Adviser).
INTRODUCTION: One reason for neglect of oral health stems from fear. An estimation of about 80% of patients has apprehension due to the pain and discomfort which is experienced from drilling. With the advancement of technology, addressing dental caries through minimum intervention is possible. One example of minimum intervention dentistry is by using a chemomechanical caries removal during caries excavation by hand. The objective of this study is to determine the efficacy of a papain-based gel from locally available papaya as a chemomechanical caries removal agent on teeth.
METHODS: The papain used in the study was acquired from Secura International Corp. It was then formulated into a gel form at the UP College of Pharmacy. The papain based gel was applied to 51 specimen teeth prior to excavation. After caries excavation using a spoon excavator, the specimen teeth were then cross-sectioned and mounted in self-curing acrylic for Vickers hardness testing. Vickers hardness number of dentin at the cavity floor was tested at two points (25μm = papain treated area; 1000μm = control).
RESULTS: Out of 51 samples, seven samples showed to be harder that that of the control group, 44 samples showed to be less hard than that of the control group. Results showed there is a statistically significant difference between the control and experimental site.
CONCLUSION: The papain based-gel can significantly reduce the hardness of the carious lesion for easier caries removal based on the Vicker's hardness number of dentin after exposure to the gel. However, due to deviations in the set protocol for the conduction of the experiment, some of the obtained values were inconsistent.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Dental caries; Chemomechanical caries removal; Papain; Papaya